Evaluability assessment: An application in a complex community improvement setting. (July 2019) - Brunner, Richard; Craig, Peter; Watson, Nick
Evaluation is essential to understand whether and how policies and other interventions work, why they sometimes fail, and whether they represent a good use of resources. Evaluability assessment (EA) is a means of collaboratively planning and designing evaluations, seeking to ensure they generate relevant and robust evidence that supports decision-making and contributes to the wider evidence base. This article reports on the context, the process undertaken and evidence from participants in an EA facilitated with public service workers involved in implementing a complex, area-based community improvement initiative. This is a novel context in which to conduct an EA. We show how the process allows practitioners at all levels to identify activities for evaluation and co-produce the theory of change developed through the EA. This enables evaluation recommendations to be developed that are relevant to the implementation of the programme, and which take account of available data and resources for evaluation.